Efficacy of Endoscopic Submucosal Dissection of Esophageal Neoplasms under General Anesthesia - Koichi Hamada; Koichiro Kawano; Atsushi Yamauchi; Ryota Koyanagi; Yoshinori Horikawa; Shinya Nishida; Yoshiki Shiwa; Noriyuki Nishino; Michitaka Honda (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Evidence that general anesthesia (GA) reduces the operative time of esophageal endoscopic submucosal dissection (ESD) is currently insufficient. This study aims to evaluate the efficacy and safety of esophageal ESD under GA. Methods A total of 227 lesions from 198 consecutive patients with superficial esophageal neoplasms treated by ESD at 3 Japanese institutions between April 2011 and September 2017 were included in this retrospective study. For ESD, GA and deep sedation (DS) were used in 102 (51.5%, GA group) and 96 patients (48.5%, DS group), respectively. Results There were no statistically significant differences in age, sex, or comorbidities between the groups. In the GA group, the tumor size was larger (21 [3-77] mm vs. 14 [3-63] mm, p<0.001), luminal circumference was larger (≥2/3; 13.9% vs. 5.4%, p=0.042), procedure time was shorter (28 [5-202] min vs. 40 [8-249] min, p<0.001), and submucosal dissection speed was faster (25.2 [7.8-157.2] mm2 /min vs. 16.2 [2.4-41.3] mm2 /min, p<0.001). The rates of intraoperative perforation and aspiration pneumonia were lower in the GA group, but the difference did not achieve statistical significance (p=0.242 and p=0.242). Conclusions GA shortens the procedure time of esophageal ESD.